2022
DOI: 10.1136/bmjopen-2022-061024
|View full text |Cite
|
Sign up to set email alerts
|

Digital multiple health behaviour change intervention targeting online help seekers: protocol for the COACH randomised factorial trial

Abstract: IntroductionUnhealthy lifestyle behaviours continue to be highly prevalent, including alcohol consumption, unhealthy diets, insufficient physical activity and smoking. There is a lack of effective interventions which have a large enough reach into the community to improve public health. Additionally, the common co-occurrence of multiple unhealthy behaviours demands investigation of efforts which address more than single behaviours.Methods and analysisThe effects of six components of a novel digital multiple he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…To avoid under-and overrecruitment, which occurs when using fixed sample sizes, is an important mitigation, and Bayesian sequential designs allow for exactly this. Examples of their use in behavioral intervention trials can be found in the literature [19][20][21][22], and when appropriate, they should become standard procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid under-and overrecruitment, which occurs when using fixed sample sizes, is an important mitigation, and Bayesian sequential designs allow for exactly this. Examples of their use in behavioral intervention trials can be found in the literature [19][20][21][22], and when appropriate, they should become standard procedure.…”
Section: Discussionmentioning
confidence: 99%